Simulation Analysis and Experimental Study of Human Lower Limb Joint Motion - Xin Zhou; Geng Liu; Bing Han; Kai Qiao; Xiaoli Liu (Jixie chuandong)
Based on the motion mechanism and biomechanics of human lower limb joints， the structure， function and motion law of human bones and joints are introduced. A simplified mathematical model of human lower limbs is established， and the posture coordinate equations of hip， knee and ankle joints are obtained. UG is used to establish the model； Adams and OpenSim are used to simulate the test； the lower limb joint angle， step height and step length curves are obtained. With the help of Xsens DOT commercial wearable sensor， the experimental results show that the simulation results are similar to the experimental results， and the joint angle， step height and step length curves are consistent with the actual human walking test results. The results show that the simplified model and simulation test are reasonable and effective and they are in line with the walking process of human lower limbs. It provides a simplified research method for sports testing， rehabilitation medicine and exoskeleton design.